Situation Analysis of Cancer Control in Indonesia - SANKARANARAYANAN, R (Indonesian Journal of Cancer, 2010)
RANGE OF ACTION TO REDUCE THE FREQUENCY,BURDEN AND IMPACT OF CANCER IN A POPULATIONÂ Full text : http://www.scribd.com/doc/43592915/Situation-Analysis-of-Cancer-Control-in-Indonesia